2013
DOI: 10.1103/physrevd.87.023532
|View full text |Cite
|
Sign up to set email alerts
|

Probing dark energy anisotropy

Abstract: Wide area cosmological surveys enable investigation of whether dark energy properties are the same in different directions on the sky. Cosmic microwave background observations strongly restrict any dynamical effects from anisotropy, in an integrated sense. For more local constraints we compute limits from simulated distance measurements for various distributions of survey fields in a Bianchi I anisotropic universe. We then consider the effects of fitting for line of sight properties where isotropic dynamics is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 75 publications
2
39
0
Order By: Relevance
“…In the models (A), the dark energy triggers the anisotropic phase. It has been argued (Appleby & Linder 2013) that next generation surveys will be capable of constraining anisotropies at the 5% level in terms of the anisotropic equation of state, which is a number to keep in mind for comparison with weak lensing.…”
Section: Observational Constraintsmentioning
confidence: 99%
“…In the models (A), the dark energy triggers the anisotropic phase. It has been argued (Appleby & Linder 2013) that next generation surveys will be capable of constraining anisotropies at the 5% level in terms of the anisotropic equation of state, which is a number to keep in mind for comparison with weak lensing.…”
Section: Observational Constraintsmentioning
confidence: 99%
“…4 Then the posterior probability density function that depends only on the cosmological parameters p is given by 1 See, e.g., [11][12][13][14][15][16][17], and [18]; also see [19]. For constraints on these and related models from near-future data see [20][21][22], and references therein. 2 For related work with growth factor data, see [23].…”
Section: A Growth Rate Of Lssmentioning
confidence: 99%
“…Similarly, it has been shown that the CMB angular power spectrum has a quadrupole power persistently lower than expected from the best-fit ΛCDM model [42,49,[51][52][53]. Several explanations for this anomaly have been proposed [22-24, 27, 28, 54-60], including the anisotropic expansion of the Universe, that could be developed well after the matter-radiation decoupling, for example, during the domination of DE, say, by means of its anisotropic pressure, acting as a late-time source of not insignificant anisotropy (see, e.g., [23][24][25][26][27][28][29][30][31][32][33][61][62][63][64][65][66] for anisotropic DE models and [67][68][69][70] for constraint studies on the anisotropic DE). On the other hand, in GR in the absence of any anisotropic source as it is the case in the standard ΛCDM, the CMB provides very tight constraints on the anisotropy at the time of recombination arXiv:1905.06949v2 [astro-ph.CO] 24 Jul 2019 [71][72][73] of the order of the quadrupole temperature fluctuation (∆T /T ) =2 ∼ 10 −5 .…”
Section: Introductionmentioning
confidence: 99%